Agronomical and breeding approaches to improve the nutritional status of forage crops for better livestock productivity. (18th January 2022) - Chand, Subhash; Indu,; Singhal, Rajesh Kumar; Govindasamy, Prabhu
Abstract: Balanced feeding to livestock can effectively convert the non‐edible forage crops into human food. Balanced output and input feeding systems further will result in greater animal health and production outcomes, with greater capacity to support growing global food demands. It also positively impacts the global economy and livelihood support of those entirely depending on livestock rearing. In general, plants are made up of carbohydrates, proteins, lipids, fibres, lignin, minerals and vitamins of varying concentrations. These nutritional components in forage crops are key determinants of livestock growth, reproduction, behaviour, productivity and end‐product quality (milk and meat etc.). A high proportion of lignin, undigested fibres, and anti‐nutritional factors (cyanogenic glucosides, Hydrogen cyanide (HCN) and condensed tannins) adversely affect the nutritional quality of forage crops. This review highlighted the importance of nutritional and anti‐nutritional components and their inter‐relationship with diverse agro‐climatic conditions. Further, we tried to cover the recent agronomical, conventional and non‐conventional breeding methods to improve the nutritional quality of forage crops concerning livestock productivity.